John Steinbeck at Glastonbury Abbey - Unknown:::Creator:::::::::::: (Somerset; England, 2022)
John Steinbeck at the excavation of Glastonbury Abbey, a monastery in Glastonbury, Somerset. From at least the 12th century the Glastonbury area has been associated with the legend of King Arthur, a connection promoted by medieval monks who asserted that Glastonbury was Avalon. In 1191 the monks alleged the discovery of King Arthur and Queen Guinevere's tomb in the cemetery. Original in safe.